Alternative measures of Family Farm Viability – Incorporating gap measures. (January 2022) - Loughrey, Jason; O'Donoghue, Cathal; Conneely, Ricky
Abstract: The measurement of farm economic viability has received intermittent academic interest with limited attention given to the conceptual framework surrounding the issue. This paper focuses attention on farm economic viability in Ireland where there are growing concerns about a two-tiered agricultural sector with increasing levels of economic vulnerability. The measurement of farm economic viability is usually based on the headcount ratio, which identifies whether a farm business is viable or non-viable and does not inform about the extent of non-viability. Therefore, it is necessary to develop alternative techniques to provide more clarity on viability levels and thereby inform assessments regarding the efficacy of the Common Agricultural Policy. This paper draws on concepts from the poverty literature to develop a viability gap measure and a viability severity measure. The results are sensitive to the choice of indicator and point to a wide distribution of viability between the most viable and least viable farms. The headcount ratio provides the basis for an incomplete assessment of viability levels and multiple indicators should be considered in monitoring viability levels. Highlights: The Farm Viability Gap is calculated using methods from the poverty literature. The Viability Gap shows wide dispersion in the viability of farms in Ireland. Farm Viability improves in disadvantaged areas of natural constraint. The 2018 summer drought has a large impact on the viability gap. Off-Farm employment is highest for the least viable 20 per cent of farms.